2020
DOI: 10.3390/polym12112576
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Phagocytic Uptake and Immunogenicity of Gliadin Nanoparticles

Abstract: The main objective of the present study was to investigate the hemo and immune compatibility of gliadin nanoparticles as a function of particle size. Gliadin nanoparticles of different size were prepared using a modified antisolvent nanoprecipitation method. The hemolytic potential of gliadin nanoparticles was evaluated using in vitro hemolysis assay. Phagocytic uptake of gliadin nanoparticles was studied using rat polymorphonuclear (PMN) leukocytes and murine alveolar peritoneal macrophage (J774) cells. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 42 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…[110,112] A too large size (e.g., >500 nm) may facilitate particle clearance by monocytes and macrophages and/or prevent the uptake of these particles by the target tumor cells. [112,113] Meanwhile, particles with a too small size (e.g., under 20 nm) are more prone to rapid renal clearance, [16,110] or cannot offer enough energy to bend cell membranes and enter the target cells. [85,111] In addition, reduced particle size leads to a larger total surface area, which may cause faster and less controlled drug release.…”
Section: Conception Of Colloidal Pecs From Hamentioning
confidence: 99%
“…[110,112] A too large size (e.g., >500 nm) may facilitate particle clearance by monocytes and macrophages and/or prevent the uptake of these particles by the target tumor cells. [112,113] Meanwhile, particles with a too small size (e.g., under 20 nm) are more prone to rapid renal clearance, [16,110] or cannot offer enough energy to bend cell membranes and enter the target cells. [85,111] In addition, reduced particle size leads to a larger total surface area, which may cause faster and less controlled drug release.…”
Section: Conception Of Colloidal Pecs From Hamentioning
confidence: 99%
“…8 c), elucidating no serious adverse effects and elucidating good biocompatibility of ZnO/WG nanospheres in vivo 42 . These results generally indicated that the administration of ZnO/WG nanospheres was biocompatible in mice 43 , 44 .
Figure 8 Safety evaluation.
…”
Section: Resultsmentioning
confidence: 55%
“…Figures 4 and 5 indicate that the nanoformulation enabled not only a reduction in the frequency of administration but also an improvement in the efficacy of KS-58. Smaller-sized nanoparticles are reportedly less immunogenic 32 , 33 . KS-58 NPs have been administered multiple times to both wild-type (Fig.…”
Section: Resultsmentioning
confidence: 99%